Methodology and problems of farm management investigations: experiences from Northern Nigeria - Norman, D. W. ([East Lansing : Dept. of Agricultural Economics, Michigan State University], 1973)
In this paper, the author describes the experiences of the Rural Economy Research Unit in carrying out village studies in Nigeria since 1965.
On cover: African rural employment study.
Bibliography: p. 46-47.
osc 05/03/2019
Loans
Keywords: Farm management; Farm management; Agriculture